NiMo-sulfide supported on activated carbon to produce renewable diesel (2017)
Due to their weak polarity and large surface area, activated carbon supports have the potential to enhance the dispersion of metal-sulfides. It is expected that the absence of a strong metal-support interaction can result in the formation of a very active and stable Ni-Mo-S phase. In this study, catalysts with different amounts of nickel and molybdenum supported on a commercial activated carbon were prepared by a co-impregnation method and characterized by BET, XRF, and SEM techniques. The catalytic activity for hydroprocessing of Jatropha oil was evaluated in a batch reactor, and the composition of the liquid and gaseous products were determined. Results showed that gaseous products are mainly composed of high amounts of propane and small amounts of other light hydrocarbons (C1 to C5). Liquid hydrocarbon products consisted of a mixture containing mainly n-paraffins of C15-C18 and some oxygenated compounds. The catalysts with a mass fraction of 3 % Ni, 15 % Mo (Ni3Mo15/AC) presented the highest selectivity toward C17-C18 hydrocarbons, with a product distribution similar to a commercial alumina-supported Ni-Mo-S catalyst.